Pemulyaan Pendidikan Perempuan Menuju Masyarakat Modern: Di Rumah Sakinah Surabaya - Nur Wahib (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2022)
The problems that befell women occur due to the imbalance of relations between men and women. Until now it is still a terrible specter. The hope for empowered women is certainly thought by many parties. Here, additional insight needs to be done so that women are empowered. So that they have a good bargaining position in various aspects of social, cultural, political and economic life that have made women trapped in stereotypes, subordination, marginalization, double burdens and violence and will be far from exploitation that has often occurred. Rumah Sakinah cannot be separated from seeing the various problems faced by the women of her nation. The large number of female members (cadres) is a big asset for Rumah Sakinah in moving and taking part from the top to the bottom level through several coordinations to deal with the context (change) of its era. Modern society is a social structure or public life environment where human relations are regulated on the basis of business, production, consumption and commercialization. In modern society, attention is more focused on the attitudes and values ??of individuals and the productivity capabilities of human resources. Therefore, the backwardness of the community (perceived) stems from internal factors of the State or the community itself, especially in the field of education.